DATABASE DESIGN IN THE CENTRALIZED NETWORK CONTROL SYSTEM BASED PT BANK NIAGA TBK WEB - Sigit Riyanto; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2008)
In the final project / thesis, the author analyzes the existing problems in the NetworkControl System PT Bank Niaga Tbk, hereinafter referred to as NCS Commercerelating to the operational network databases owned. NCS Commerce is a division ofPT Citra Sari Makmur has a duty and responsibility in guarding, maintaining datacommunications network and providing service in the field of IT (Information andTechnology) to PT Bank Niaga Tbk. as one of the customers who use the services ofdata communication services. NCS Commercial located at two different locations ofthe data center and data center Cikarang Commerce Commerce Bintaro require acentralized database and can provide accurate and current data to support operationalactivities of the NCS Commerce. Currently the database is still in the form of anexcel file (spreadsheet) that is independent and is available at each location NCSCommerce, resulting in duplication of data, inaccurate and not current. To the authorstry to make a design and build web-based centralized database systems using PHP 5.0and the MySQL database that is expected to provide a centralized database systemsare accurate and up to date and easily accessible by each site with the support of NCSCommerce Internet network owned. As the data supporting the authors also makedirect observation in PT. Citra Sari Makmur, especially in the NCS DivisionCommerce.